Reasoning with Linear Orders: Differential Parietal Cortex Activation in Sub-Clinical Depression. An fMRI Investigation in Sub-Clinical Depression and Controls - Hinton, Elanor C.; Wise, Richard G.; Singh, Krish D.; von Hecker, Ulrich (Frontiers in Human Neuroscience, 2015)
The capacity to learn new information and manipulate it for efficient retrieval has long been studied through reasoning paradigms, which also has applicability to the study of social behaviour. Humans can learn about the linear order within groups using reasoning, and the success of such reasoning may vary according to affective state, such as depression. We investigated the neural basis of these latter findings using functional neuroimaging. Using BDI-II criteria, 14 non-depressed and 12 mildly depressed volunteers took part in a linear-order reasoning task during fMRI. The hippocampus, parietal and prefrontal cortices were activated during the task, in accordance with previous studies. In the learning phase and in the test phase, greater activation of the parietal cortex was found in the depressed group, which may be a compensatory mechanism in order to reach the same behavioural performance as the non-depressed group, or evidence for a different reasoning strategy in the depressed group.